Online publishing in Kenya: factors contributing to self-publishing - Ayan, Mohamed Yusuf (2022)
Self-publishing is an emerging trend in the Kenyan publishing industry. Technological advancements particularly online publishing, e-book publishing services, and print-ondemand have enabled authors the opportunity to publish their books. However, there is a significant knowledge gap pertaining to self-publishing in Kenya. This research aims to examine factors influencing the self-publishing of books in Kenya, including how selfpublishing enhances the autonomy of the Kenyan self-published authors, their challenges, and their proposed solutions. Using qualitative approach, ten Kenyan self-published authors participated in a one-on-one interview until a saturation level was reached. Overall, the study disclosed that various political economy factors faced by these self-published fiction book authors including the power of mainstream publishing, authors’ freedom and autonomy over their self-published books, royalties, stocking at bookstores, affordable shipping, costeffective printing and availability of independent publishers. Challenges faced by Kenyan self-published authors consisted of fatigue, lack of financial support, poor marketing, and rejection from both established bookstores and publishing companies.